Accounting Conservatism and Performance Covenants: A Signaling Approach - Callen, Jeffrey L.; Chen, Feng; Dou, Yiwei; Xin, Baohua (Contemporary Accounting Research, 2015)
This study examines the relation between performance covenants in private debt contracting and conservative accounting under adverse selection. We find that under severe adverse selection (i.e., high information asymmetry), accounting conservatism and performance covenants act as complements to signal that the borrower is unlikely to appropriate wealth from the lender. No such relation obtains in a low information asymmetry regime. We further show that in the high information asymmetry regime, borrowers with high levels of conservatism and tight performance covenants generally enjoy lower interest rate spreads than borrowers with low levels of conservatism and loose performance covenants. Consistent with our signaling theory, in the high information asymmetry regime, borrowers with high levels of conservatism and tight performance covenants are less likely to make abnormal payouts to shareholders. Our empirical results are robust to alternative measures of conservatism and covenant restrictiveness.